Alternative Splicing of AMPA Subunits in Prefrontal Cortical Fields of Cynomolgus Monkeys Following Chronic Ethanol Self-Administration - Acosta, Glen; Friedman, David P.; Grant, Kathleen A.; Hemby, Scott E. (Frontiers in Psychiatry, 2012)
Functional impairment of the orbital and medial prefrontal cortex underlies deficits in executive control that characterize addictive disorders, including alcohol addiction. Previous studies indicate that alcohol alters glutamate neurotransmission and one substrate of these effects may be through the reconfiguration of the subunits constituting ionotropic glutamate receptor (iGluR) complexes. Glutamatergic transmission is integral to cortico-cortical and cortico-subcortical communication and alcohol-induced changes in the abundance of the receptor subunits and/or their splice variants may result in critical functional impairments of prefrontal cortex in alcohol dependence. To this end, the effects of chronic ethanol self-administration on glutamate receptor ionotropic AMPA (GRIA) subunit variant and kainate (GRIK) subunit mRNA expression were studied in the orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) of male cynomolgus monkeys. In DLPFC, total AMPA splice variant expression and total kainate receptor subunit expression were significantly decreased in alcohol drinking monkeys. Expression levels of GRIA3 flip and flop and GRIA4 flop mRNAs in this region were positively correlated with daily ethanol intake and blood ethanol concentrations averaged over the six months prior to necropsy. In OFC, AMPA subunit splice variant expression was reduced in the alcohol treated group. GRIA2 flop mRNA levels in this region were positively correlated with daily ethanol intake and blood ethanol concentrations averaged over the six months prior to necropsy. Results from these studies provide further evidence of transcriptional regulation of iGluR subunits in the primate brain following chronic alcohol self-administration. Additional studies examining the cellular localization of such effects in the framework of primate prefrontal cortical circuitry are warranted.